2012
DOI: 10.1002/app.38496
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of oxidative stabilization of viscose rayon fibers impregnated with ammonium sulfate prior to carbonization and activation steps

Abstract: The oxidative thermal stability of microcrystalline plant-based viscose rayon cellulose fiber was improved in the presence of an ammonium sulfate solution. The structural characterization of the oxidized samples was carried out using a combination of fiber thickness, linear density, burning test, X-ray diffraction (XRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and infrared (IR) spectroscopy measurements. Oxidized viscose rayon fibers showed physical and chemical transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Typically performed by applying these flame retardants to a precursor by passing the tow through a solution in water before drying (Morgan 2005), Karacan et al showed that rayon fibres treated with a mixture of phosphorus and boric acid significantly improved oxidative stability while reducing the evolution of volatile compounds. However, no specific details in regards to the stabilisation mechanism, carbon yield or stabilisation rate was discussed (Karacan and Soy 2013). Byrne et al treated regenerated cellulose samples with a phosphorus-based ionic liquid showing a significant improvement in the carbon yield (50% remaining after carbonisation at 500°C).…”
Section: Introductionmentioning
confidence: 99%
“…Typically performed by applying these flame retardants to a precursor by passing the tow through a solution in water before drying (Morgan 2005), Karacan et al showed that rayon fibres treated with a mixture of phosphorus and boric acid significantly improved oxidative stability while reducing the evolution of volatile compounds. However, no specific details in regards to the stabilisation mechanism, carbon yield or stabilisation rate was discussed (Karacan and Soy 2013). Byrne et al treated regenerated cellulose samples with a phosphorus-based ionic liquid showing a significant improvement in the carbon yield (50% remaining after carbonisation at 500°C).…”
Section: Introductionmentioning
confidence: 99%
“…10 Indeed ILs have themselves been shown to be excellent carbon precursors. 11,12 Typically impregnate chemicals are based on nitrogen, sulfur and phosphorus 9,13 containing compounds as such we have focused our attention on the following ILs: triethylammonium phosphate [TEA]H 2 PO 4 , triethylammonium hydrogen sulphate [TEA]HSO 4 , 1-methyl imidazolium phosphate [HMIM]H 2 PO 4 , 1-methyl imidazolium hydrogen sulfate [HMIM]HSO 4 and cholineH 2 PO 4 . We also included 2 phosphonium ILs, tributyl(ethyl)phosphonium diethylphosphate CYPHOS IL 169 and tributyl(methyl)phosphonium methylsulfate, CYPHOS IL 108 since the thermal degradation temperature of these ILs is better than the imidazolium ILs.…”
mentioning
confidence: 99%
“…Fig. 3a shows the 13 C NMR spectra and Fig. 3b shows the XRD spectra of the carbonized samples impregnated with [TEA]-H 2 PO 4 , [HMIM]H 2 PO 4 and cholineH 2 PO 4 , respectively.…”
mentioning
confidence: 99%
“…[26] The modifi cation of NWVR with PPy forms a hydrogen bond with hydroxyl group (as discussed before) will make a selective decrystallisation (amorphisation) of (1I -0) plane, which will cause the decrease in the intensity in the (1I -0) plane. [27] The gradual decrease in intensity at (1I -0) plane upon increase in PPy concentrations is observed and it indicates the increase in this selective amoprhistion due to polymerisation ( Figure S6A). To fi nd the temperature effect on crystallographic structure, we performed XRD analysis for preheated (analysis performed immediately after 5 mins heating) samples.…”
Section: Doi: 101002/admi201300139mentioning
confidence: 87%